2(x-3)-(x-2)=5

Question

Asked 3/17/2009 9:54:10 AM

Updated 12/1/2014 5:08:27 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [12/1/2014 5:07:36 AM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Expert answered|plumautoworks|Points 115|

Question

Asked 3/17/2009 9:54:10 AM

Updated 12/1/2014 5:08:27 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [12/1/2014 5:07:36 AM]

Rating

8

2(x - 3) - (x - 2) = 5;

(2x - 6) - (x - 2) = 5;

x - 4 = 5;

x = 5 + 4;

x = 9

(2x - 6) - (x - 2) = 5;

x - 4 = 5;

x = 5 + 4;

x = 9

Added 12/1/2014 5:08:27 AM

This answer has been confirmed as correct and helpful.

x--8=5

Question

Expert Answered

Updated 3/24/2014 6:52:56 AM

3 Answers/Comments

Wouldn't the answer be -3? When you have two negatives like that they become positive and when you bring them to the other side 8 becomes a negative. So -8 +5=-3.

Added 3/17/2009 11:17:15 AM

5(x+2)-3(x-5)=29
**Weegy:**
5(x + 2) - 3(x - 5) = 29;
(5x + 10) - (3x - 15) = 29;
2x + 25 = 29;
2x = 29 - 25;
2x = 4;
x = 4/2;
x = 2
(More)

Question

Expert Answered

Updated 12/1/2014 5:06:49 AM

0 Answers/Comments

2(x+2)+3(x+4)=31 **Weegy:** Simplifying
x = -4 **User:** can you show me the working? so i know how to do it? **Weegy:** Can you repeat your question plse? (More)

Question

Expert Answered

Updated 12/1/2014 5:04:28 AM

1 Answer/Comment

2(x + 2) + 3(x + 4) = 31;

2x + 4 + 3x + 12 = 31;

5x + 16 = 31;

5x = 31 - 16;

5x = 15;

x = 15/5;

x = 3

2x + 4 + 3x + 12 = 31;

5x + 16 = 31;

5x = 31 - 16;

5x = 15;

x = 15/5;

x = 3

Added 12/1/2014 5:04:27 AM

This answer has been confirmed as correct and helpful.

39,064,491

questions answered

There are no comments.